Achieving objectivity while checking students' written assignments - Olga M. Kochkina (Russian Journal of Education and Psychology)
Background. The problem of achieving objectivity while grading students’ papers is constantly under discussion in the pedagogical community. In this respect the issue of teachers’ qualification is sure to come to the foreground. However, scientific interest may arise in studying other, both subjective and objective, factors that could induce the teacher to downgrade, as well as upgrade the student’s mark.